The role of climatic variability on the short-term fluctuations of octopus captures at the Canary Islands - Caballero Alfonso, Ángela María; Ganzedo López, Unai; Trujillo-Santana, Aarón; Polanco, J.; Santana del Pino, A.; Ibarra-Berastegi, G.; Castro-Hernández, J. J. (Fisheries Research, 2010)
The effect of temperature on the common octopus life cycle has been well studied. However, how other climatic patterns affect them is poorly understood. The present work emphasises the importance of the temperature on common octopus catches by the small-scale trap fishery off the Canary Islands, and also highlights the effect of the North Atlantic Oscillation (NAO) pattern. As well as an inverse and significant correlation between octopus abundance (measured as CPUE) and Sea Surface Temperature (SST), a direct relationship between abundance and NAO, off the Canary Archipelago, is reported. Using a linear model (lm) with a stepwise procedure, SST is found to be the most important and significant variable in autumn, accounting for 34.21%. Meanwhile, the NAO became more important in spring with 28.64% and a 31.13% of the explained variance in autumn.